Groups versus individuals in the determination of caribou distribution - Whitten, K. R.; Cameron, R. D. (Rangifer, 1986)
Studies of caribou (Rangifer tarandus) habitat selection based on group analyses have led to erroneous conclusions. Convenient designations such as «male-» or «female-dominated» group encompass a wide array of possible sizes and compositions which change continuously and erratically. Whenever individuals of at particular sex/age class can occur in more than one group type, and/or whenever groups within a type vary in size, an analysis based on groups alone is fallacious. Data must be based on individual caribou for most, if not all, determinations of distribution.